The Brigade : An Epic Story of Vengeance, Salvation, and World War II - Blum, Howard (New York Simon & Schuster, 2001)
A story of three soldiers who served in a Jewish fighting force against the Nazis in the autumn of 1944. Initially about vengence as the men faced the atrocities of the Nazi regime, the story is ultimately about salvation. The men went off to kill but wound up saving thousands of lives.
Include Illustrations and Notes on Sources.
An Epic Story of Vengeance, Salvation, and World War II.
Keywords: World War (1939-1945) -- Military participation--Jewish -- Middle East--Palestine -- Jewish soldiers